Preliminary workflow for subsurface fracture mapping using 3D seismic surveys: A case study from the Cooper Basin, South Australia - Abul Khair, H.; Cooke, D.; King, R.; Hand, M.; Tingay, Mark (2012)
The future success of both enhanced (engineered) geothermal systems and shale gas production relies significantly on the development of reservoir stimulation strategies that suit the local stress and mechanical conditions of the prospects. The orientation and nature of the in-situ stress field and pre-existing natural fracture networks in the reservoir are amongst the critical parameters controlling the success of any stimulation program. This work follows an initial study showing the existence of natural fractures in the area covered by the Moomba-Big Lake 3D seismic survey, in the South-Western termination of the Nappamerri Trough of the Cooper Basin in South Australia. The fractures, imaged both by borehole image logs and seismic attributes (Most Positive Curvature and Ant tracking), are pervasive across the seismic survey, and present a relatively constant NW-SE orientation. We processed and analyzed the 3D seismic cube, Moomba-Big Lake survey in the Cooper Basin. Most positive curvature attribute (MPC) was then calculated from a structurally smoothed, non-steered version of the seismic cube. Comparing the curvature signatures with the seismic amplitude signatures indicated that all the curvature values = 0.2 are mapping structural features that enhance fracture stimulation (i.e. faults and folds). A new cube with curvature values = 0.2 was then generated, and the ant tracking technique was applied to the final cube. We calibrated the resulting cube using seismic amplitudes, image logs, and well data and a highly positive correlation was found. Also, analysis shows that under present day stress orientation and magnitudes, fractures striking NW-SE and NE-SW are more susceptible to stimulation, and are more likely to open for fluid flow. Accordingly, the current procedure provided a solution for mapping structural features pre-drilling, which affect reservoir porosity and permeability and will help developing stimulation strategies.